2022
DOI: 10.3390/ijms231911574
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Lipid Metabolism in the Hepatopancreas of Shrimp Litopenaeus vannamei upon Light and Heavy Infection of Enterocytozoon hepatopenaei: A Comparative Proteomic Study

Abstract: Enterocytozoon hepatopenaei (EHP) is the pathogen of hepatopancreatic microsporidiosis (HPM) in shrimp. The diseased shrimp Litopenaeus vannamei exhibits a slow growth syndrome, which causes severe economic losses. Herein, 4D label-free quantitative proteomics was employed to analyze the hepatopancreas of L. vannamei with a light (EHPptp2 < 103 copies/50 ng hpDNA, L group) and heavy (EHPptp2 > 104 copies/50 ng hpDNA, H group) load of EHP to better understand the pathogenesis of HPM. Exactly 786 (L group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…The color of hepatopancreas and intestine turned white, which is a signal of EHP infection. This phenomenon may be related to lipid reduction in the crab and shrimp (Ding, 2021; Wu et al, 2022), and the presence of a large number of spores in the P. clarkii (Fig. 1 B & C; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The color of hepatopancreas and intestine turned white, which is a signal of EHP infection. This phenomenon may be related to lipid reduction in the crab and shrimp (Ding, 2021; Wu et al, 2022), and the presence of a large number of spores in the P. clarkii (Fig. 1 B & C; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The primer sets targeting universal for microsporidia and EHP polar tube protein 2 ( EHPptp2 ) were used to identify the infection of EHP (Zhu et al, 1993; Baker et al, 1995; Wang et al, 2021; Wu et al, 2022). Two pairs of primers amplifying mitochondrial genes were employed to identify the crayfish (Folmer et al, 1994; Li et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Horizontally transmitted parasites are generally linked to high virulence, which might reduce host fitness. For instance, Enterocytozoon hepatopenaei, a microsporidian belonging to the Enterocytozoonida clade, infects the hepatopancreas of various shrimps inducing storage consumption of lipids, downregulation of lipid metabolism and thus energy production 85 . It is, therefore, plausible that a reduction in fitness might occur and hinder the ability of G. pulex to withstand water flow and, thus, be more likely found in the drift.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of EHP spores in the hepatopancreas and midgut indicates an oral route of transmission, which could either result from immersion, swallowing pathogen-infected water, active cannibalism, or the consumption of infected shrimp [ 3 , 5 ]. A recent analysis of the 3.26 Mbp EHP genome revealed that the pathogen could not generate ATP either viaglycolysis or oxidative phosphorylation [ 6 , 7 ]. EHP, therefore, obtains ATP and other purine nucleotides for energy and biosynthesis from their host by using nucleotide transport (NTT) proteins, which are acquired via lateral gene transfer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%